W niewoli mediow : przewodnik dla odbiorcow prasy, radia, telewizji, kina, wideo - Czarniecki, Mariusz (Warszawa : Wydawn. Antyk Marcin Dybowski, 1997)
A Polish journalist reflects upon the madness of the mass media in Poland and upon its social aspects.
Keywords: Mass media -- Social aspects -- Poland